فعالية الطريقة الإيحائية في ترقية مهارة الكلام عند طالبات المعهد العالي للدراسات الإسلامية واللغة العربية مكسر في قسم الإعداد اللغوي - Syamsiah Nur; Haniah Haniah; Munir Munir (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2022)
This study aims to examine the effectiveness of suggestopedia method in improving the students’ speaking skill at the Language Preparation Program of College of Islamic Studies and Arabic Language (STIBA) Makassar. The methodological used in this study was quantitative experimental research by using a pre-experimental design. The data collection method used in the study were observation, test and documentation. The data analysis was conducted through descriptive analysis and inferential statistics by using the (t-test) technique. Therefore, the researcher conducted both pre and post tests so that the effectiveness of the suggestopedia method on students’speaking skill could be carefully determined. The results of the study with implementation of suggestopedia method were in the avarge of 0.000 which was considered to be smaller than 0.05. This indicates significant influence on students’ speaking skill using the suggestopedia method.